Psychological features of experience of fear in primary school children and adolescents from complete and incomplete families (The Journal of Psychology and Sociology, 2015)
The article presents an analysis of modern studies of the concept of fear, its types and causes. It was determined that the fear is a basic human emotions, which indicates the status of risk depends on many external and internal, of congenital or acquired factors. The causes of fear, accord ing to scientists, psychologists, is a particularly family upbringing style of family relationships, social conditions of child development. Consider the concept of incomplete family and psychological characteristics of students from singleparent families. The results of empirical studies of the experi ence of fear in primary school children and adolescents from complete and incomplete families. It was revealed that in primary school children and adolescents from singleparent families the number of manifestations of fear more than the younger students and adolescents from intact families; and the level of anxiety is higher in singleparent families representatives. The description of the training to work with fear and anxiety in primary school children and adolescents.
Keywords: emotional sphere; fear; anxiety; complete and incomplete family; younger school age; adolescence; training.